Pengaruh Intensitas Belajar Dan Modal Sosial Terhadap Hasil Belajar Mata Pelajaran Administrasi Transaksi Pemasaran di SMK Negeri 2 Pariaman - Syawirda Syawirda; Yulhendri Yulhendri (Jurnal Ecogen, 2019)
The research aims to determine the effect of learning intensity and social capital to result of learning of students at state vocational high school 2 of Pariaman in academic year 2019/2020. The population in this research was all students of class XI until XII. The sample use are 107 with proportional random sampling technique. The analytical method used is multiple regression analysis using the SPSS version 20 program. This research use asosiatif method with deskriptive analysis. The data is analyted by using multiple regression. The result show that 1) There were a learning intensity and social capital to results of  learning of students (F sig = 0,000 < dari 0,05). 2) There was a effect between learning intensity to result of  learning (sig = 0,001< 0,05). 3) There was a effect between social capital to result of  learning (sig = 0,000< 0,05).   Keywords: intensity of learning, social capital, result of learning